Investigation of abrasive saw kickback. Issue 1 (2nd January 2022) - Burcat, Steven; Yue, Brian; Slocum, Alexander; Cohen, Tal
Abstract : Saw kickback can cause fatal injuries, but only woodcutting saws have regulations and assessment methodologies for kickback. These regulations do not apply to abrasive cutting saws, as their cutting mechanism and dominant kickback mode differ from those of woodcutting saws. This work combines theoretical and experimental tools to investigate abrasive saw kickback. A theoretical model based on frictional engagement during a pinch-based kickback event is shown to predict resultant kickback energy in good agreement with experimental measurements. These measurements were obtained using a specialized machine that generates pinch-based kickback events and measures resultant kickback energy. Upon validating the model, two representative saws, a circular cutoff saw and a chainsaw, were tested using the prototype machine to evaluate their comparative kickback risk. This work demonstrates that pinch-based kickback is a potential safety risk for abrasive cutting saw operators and provides a testing machine design and analytical framework for evaluating this risk.